Perencanaan dan Pengembangan Perangkat Ajar Matematika dalam Implementasi Kurikulum Merdeka di SMA Negeri 12 Padang - Lailatul Rahmi; Nita Putri Utami (International Forum of Researchers and Lecturers, 2025)
This study aims to describe the process of planning Mathematics learning at SMA Negeri 12 Padang in implementing the Independent Curriculum. A descriptive qualitative approach was used with interview techniques and observations of Mathematics teachers. The results of the study showed that teaching tools, such as teaching modules, assessments, remedial programs, enrichment, olympiads, textbooks, teaching materials, and LKPD, were arranged systematically and adaptively according to student needs. Based on the results of observations, the teaching tools achieved a success percentage of 98.54% in grades X and XI. The teaching tools support meaningful, contextual learning, and improve student competence. Evaluation and development of teaching tools are carried out continuously to be relevant to curriculum developments.